HUKUM ACARA E-LITIGASI DAN PENERAPANNYA DI PENGADILAN AGAMA SAMPIT - Rahmatiah, Rahmatiah; Ahmad, Sabarudin (Sharia Faculty of State Islamic Institute (IAIN) Palangka Raya, 2023)
This research was motivated by the Sampit Religious Court which has the least number of e-litigation cases compared to another religious court in the Central Kalimantan Province. The aim of this research is to find out the e-litigation process at Sampit Religious Court and the response of the society towards the E-litigation proceedings at Sampit Religious Court. This research is qualitative research using an empirical juridical approach. The result of this research showed that the procedure for settling cases that carried out electronically or known as e-litigation at the Sampit Religious Court was based on Sepreme Court Regulation Number 1 of 2019. The response of the society toward e-litigation proceedings in Sampit Religious Court categorized as low response because many people prefer conventional trials by going to the court directly.